2010
DOI: 10.1002/bse.668
|View full text |Cite
|
Sign up to set email alerts
|

The use of real options valuation methodology in enhancing the understanding of the impact of climate change on companies

Abstract: Climate change has in recent years gathered traction on the business, political and social agenda. From the business perspective, research has shown that climate change impacts on company value are uncertain, signifi cant and strategically important. The challenge therefore is for the business community to apply fi nancial valuation models that support the incorporation of the climate change impacts in strategic planning. However, the commonly used discounted cash fl ow techniques in capital budgeting are seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
2
7
0
1
Order By: Relevance
“…While research into organizational responses to climate change has found that companies are increasingly becoming aware of risks related to greenhouse gas emissions, and many take appropriate response measures (e.g. Kolk and Pinkse, ; Jeswani, Wehrmeyer and Mulugetta, ; Brouhle and Harrington, ; Pinkse and Kolk, ; Tyler and Chivaka, ; Weinhofer and Hoffmann, ; Vespermann and Wittmer, ; Lee, ), our study focuses on the corporate management of climate risks. Our case studies illustrate that the degree of concern over the physical effects of climate change varies between companies.…”
Section: Discussionmentioning
confidence: 99%
“…While research into organizational responses to climate change has found that companies are increasingly becoming aware of risks related to greenhouse gas emissions, and many take appropriate response measures (e.g. Kolk and Pinkse, ; Jeswani, Wehrmeyer and Mulugetta, ; Brouhle and Harrington, ; Pinkse and Kolk, ; Tyler and Chivaka, ; Weinhofer and Hoffmann, ; Vespermann and Wittmer, ; Lee, ), our study focuses on the corporate management of climate risks. Our case studies illustrate that the degree of concern over the physical effects of climate change varies between companies.…”
Section: Discussionmentioning
confidence: 99%
“…First, it aims to assist policymakers, investors and managers of corporations in improving their understanding of the link between climate change policy commitments and the corporate response to them. This is in line with a number of authors highlighting the need for such information for improving the decision‐making of managers, investors and policy‐makers for climate change related issues (Pfeifer and Sullivan, ; Tyler and Chivaka, ).…”
Section: Discussionmentioning
confidence: 99%
“…This information is important for corporations to design essential GHG management practices as well as for public policy entities to improve their knowledge of the effectiveness of their climate change policies on corporate behavior. The success of these accounting models requires suitable financial valuation techniques to determine the effects of climate change on firms' assets (Tyler and Chivaka, ). However, the present informal nature of accounting standards and the differing types of financial and non‐financial information used by current accounting models make the use of such models untrustworthy and complicated for both corporations and public policy entities.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques, such as real options valuation have been indicated as having potential to enhance the understanding of impacts by handling uncertainties directly (Tyler and Chivaka, 2011). Studies have shown that companies are reluctant to use real options valuation (Peel and Bridge, 1998;Sandahl and Sjogren, 2002;Block, 2003;Hermes et al, 2007and Truong et al, 2008, although a recent study conducted by Hall and Millard (2010) showed that this methodology is often used in South African companies.…”
Section: Introductionmentioning
confidence: 99%